Cigarette smoke alters the secretome of lung epithelial cells. Issue 1 (January 2017) - Mossina, Alessandra; Lukas, Christina; Merl‐Pham, Juliane; Uhl, Franziska E.; Mutze, Kathrin; Schamberger, Andrea; Staab‐Weijnitz, Claudia; Jia, Jie; Yildirim, Ali Ö.; Königshoff, Melanie; Hauck, Stefanie M.; Eickelberg, Oliver; et al.
Abstract : Cigarette smoke is the most relevant risk factor for the development of lung cancer and chronic obstructive pulmonary disease. Many of its more than 4500 chemicals are highly reactive, thereby altering protein structure and function. Here, we used subcellular fractionation coupled to label‐free quantitative MS to globally assess alterations in the proteome of different compartments of lung epithelial cells upon exposure to cigarette smoke extract. Proteomic profiling of the human alveolar derived cell line A549 revealed the most pronounced changes within the cellular secretome with preferential downregulation of proteins involved in wound healing and extracellular matrix organization. In particular, secretion of secreted protein acidic and rich in cysteine, a matricellular protein that functions in tissue response to injury, was consistently diminished by cigarette smoke extract in various pulmonary epithelial cell lines and primary cells of human and mouse origin as well as in mouse ex vivo lung tissue cultures. Our study reveals a previously unrecognized acute response of lung epithelial cells to cigarette smoke that includes altered secretion of proteins involved in extracellular matrix organization and wound healing. This may contribute to sustained alterations in tissue remodeling as observed in lung cancer and chronic obstructive pulmonary disease.